Along Beach Management Strategy in Improving the Economy of the Along Village Community in Simeulue - Baihaqi, Baihaqi; Saputra, Redi (Teunuleh Publisher, 2024)
This research focuses on the management strategy of Along Beach to improve the economy of the community of Along Village, Salang District, Simeulue Regency. The main objective of the study is to understand management strategies and the factors that support and inhibit such management. The method used is qualitative, with data collection through observation, interviews, and documentation. The object of the study involved seven informants, including the Head of the Tourism Office and visitors to Along Beach. The strategies implemented include tourism promotion through social media, training to improve the quality of human resources, and the provision of adequate facilities. Community involvement, such as Agam Inong Simeulue in tourism promotion, also contributes to the improvement of the local economy by creating job and business opportunities. Supporting factors for the management of Along Beach include exotic scenery and good accessibility. However, there are several obstacles, such as lack of hygiene awareness among visitors, budget limitations, and inadequate parking lots. This study shows that effective management can reduce unemployment and increase the income of the community around Along Beach.